Altitudinal distribution of apomixis in the high-alpine flora of the Ladakh, NW Himalaya - Brožová, Viktorie (Jihočeská univerzita, 2015)
Apomixis is a specific way of asexual plant reproduction by seeds. Conversion from sexual reproduction to apomixis is enabled by many different factors. These include molecular changes in DNA, changes on chromosomes, or affinity to certain taxonomical lineages. Even ecological conditions, as stressful high altitude or latitude environment, are thought to be factors capable of turning sexuality into apomixis. To test this hypothesis, we collected seeds of angiosperms from Indian part of Himalayas, in Ladakh. The seeds were analysed by FCSS where ratio of genome sizes of endosperm / embryo revealed type of reproduction system. Our data indicated 9 apomictic species from 232 totally measured species. These were Biebersteinia odora, Potentilla gelida, P. pamirica, P. sericea, P. sojakii, P. venusta, Poa attenuata, Ranunculus membranaceus and Stipa splendens. Most of the apomicts are known from previous studies or they have closely related apomictic species. Just Biebersteinia odora has no known related apomicts because of missing data about reproduction systems in this family. This results showed rather no affinity of apomictic species to high elevations; apomixis is more likely bound in taxonomically related groups. Our measurement provide extensive dataset to establish relative ratio of size of endosperm / embryo for individual families; this dataset may serve as valuable comparative material in following studies dealing with FCSS.
Altitudinal distribution of apomixis in the high-alpine flora of the Ladakh, NW Himalaya